Biomedical Advances in HIV Prevention Social and Behavioral Perspectives - Eaton, Lisa A.; Kalichman, Seth C.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Biomedical Advances in HIV Prevention: Social and Behavioral Perspectives   Lisa A. Eaton and Seth C. Kalichman, editors     Three decades into the epidemic, a great deal is known about HIV and its transmission, more people are living with the disease, and the virus is no longer seen as a death sentence. But new people continue to be infected with HIV each year, making prevention strategies that are medically effective and behaviorally engaging as urgent a priority as ever.   Biomedical Advances in HIV Prevention: Social and Behavioral Perspectives assembles the latest improvements, barriers to implementation, and possibilities for--and challenges to--future progress. Innovations such as pre-exposure prophylaxis (antiretroviral regimens for the high-risk uninfected) and treatment as prevention (early use of ART to reduce infectiousness of new patients) are examined, as are current findings on ongoing prevention and treatment concerns. Contributors illuminate the complex realities entailing adherence, pointing out technological, behavioral, and cultural roadblocks as well as opportunities to significantly reduce infection rates. Detailed up-to-the-minute coverage includes:   Prevention services for persons living with HIV Adherence to HIV treatment as prevention and pre-exposure prophylaxis Advocating for rectal microbicides and safe lubricants Mental health and substance use in the scale-up of HIV prevention Risk compensation in response to HIV prevention Implementing biomedical HIV prevention advances: reports from South Africa, Uganda, Australia, Thailand, United States, Ecuador, and Peru   Researchers, practitioners, and policy makers working in the fields of HIV/AIDS and public health will look toward Biomedical Advances in HIV Prevention: Social and Behavioral Perspectives as both a means for developing and assessing current programs and a blueprint for the next generation of prevention efforts.
Part I. Advances in HIV Prevention Technologies -- Chapter 1: Advances, Promises, and Challenges in HIV Prevention -- Chapter 2: Pre-Exposure Prophylaxis -- Chapter 3: Prevention Services with Persons Living with HIV -- Chapter 4: Advocating for Rectal Microbicides and Safe Lubricants -- Part II. Behavioral Challenges and Opportunities -- Chapter 5: Adherence to HIV Treatment as Prevention and Pre-Exposure Prophylaxis -- Chapter 6: Risk Compensation in Response to HIV Prevention -- Chapter 7: Mental Health and Substance Use in the Scale Up of HIV Prevention -- Chapter 8: Substance Use Treatment in the Era of New HIV Prevention Technologies -- Part III. Global Perspectives -- Chapter 9: Revolution or evolution? What can approaches based on the use of antiretroviral drugs contribute to HIV prevention in gay communities in high-income countries? -- Chapter 10: Implementing Biomedical HIV Prevention Advances in Uganda -- Chapter 11: Implementing Biomedical HIV Prevention Advances in Thailand -- Chapter 12: Implementing Biomedical HIV Prevention Advances in Ecuador and Peru.
Keywords: Public health; Health promotion; Public Health; Health Promotion and Disease Prevention